The Influence of Foreign Direct Investment on Employment in Visegrad Group Countries - Stępniewski-Janowski, Franciszek Jerzy (2022)
Foreign direct investment is an essential factor for developing economies as it provides both tangible and intangible factors to the development of the economy. The second important indicator of economic development is the labour market. Therefore, the following thesis examines the influence of the FDI on employment. It follows the current research findings regarding the effects and determinants of both FDI inflows and employment rates. The effects are examined for the Visegrad Group Countries. The thesis provides a graphical analysis of data on FDI and determinants of the labour market (employment, unemployment rates). However due to complex of the examined issue the findings cannot support the hypothesis that FDI influences employment